Airway function at one year: association with premorbid airway function, wheezing, and maternal smoking. Issue 9 (1st September 2001) - Dezateux, C; Stocks, J; Wade, A M; Dundas, I; Fletcher, M E
Abstract : BACKGROUND: Impaired growth and development of the respiratory system during fetal and early postnatal life may have important implications for lung development and later lung health. The aim of this study was to examine the association of diminished premorbid airway function, prior wheezing, and maternal smoking with airway function at 1 year of age. METHODS: Respiratory function was measured at the end of the first year in 100 of 108 healthy term infants (93%) in whom similar measurements had been undertaken prior to any respiratory illness at 8 weeks. Physician diagnosed wheezing episodes were identified retrospectively from medical records. RESULTS: At 1 year specific airway conductance during end expiration (sGawee ; /s/kPa) was significantly diminished in those infants with prior wheezing (95% CI wheeze/no wheeze –0.76 to –0.14), mothers who smoked (95% CI smoke/no smoke –0.81 to –0.27), a family history of asthma (95% CI family history/no family history –0.62 to 0.00), or diminished premorbid sGawee (95% CI –0.13 to –0.43/s/kPa per unit reduction sGawee at 8 weeks). In a multivariate model only maternal smoking and diminished premorbid sGawee were independently associated with diminished sGawee at 1 year. CONCLUSIONS: Diminished airway function at the end of the first year appears to be mediated by impaired airway development during early life as well as by exposure to maternal smoking. These findings are consistent with the hypothesis that, at a population level, diminished premorbid airway function provides the link between wheezing lower respiratory illness and diminished airway function at 1 year. Maternal smoking remains an important and avoidable cause of impaired airway development and function in infancy.